Developmental relocation of presynaptic terminals along distinct types of dendritic filopodia - Evers, Jan-Felix (Developmental biology, 2006)
Dendritic filopodia are long thin protrusions occurring predominantly on developing neurons. Data from different systems suggest a range of crucial functions for filopodia in central circuit formation, including steering of dendritic growth, branch formation, synaptogenesis, and spinogenesis. Are the same filopodia competent to mediate all these processes, do filopodia acquire different functions through development, or do different filopodial types with distinct functions exist? In this study, 3-dimensional reconstructions from confocal image stacks demonstrate the existence of two morphologically and functionally distinct types of filopodia located on the dendritic tips versus the dendritic shafts of the same developing motoneuron. During dendritic growth, both filopodial types undergo a process of stage-specific morphogenesis. Using novel quantification strategies of 3-dimensional co-localization analysis for immunocytochemically labeled presynaptic specializations along postsynaptic filopodia, we find that presynaptic terminals accumulate along filopodia towards the dendrites at both stable dendritic shafts and on growing dendritic tips. On tips, this is likely to reflect synaptotrophic growth of the dendrite. At stable shafts, however, presynaptic sites become relocated along filopodia towards dendritic branches. This indicates the interactive growth of both pre- and postsynaptic partner towards one another during synaptogenesis, using filopodia as guides.